HUBUNGAN BUDAYA ORGANISASI DENGAN MOTIVASI KERJA GURU SEKOLAH DASAR NEGERI GUGUS I, II DAN III KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU RIAU - Elva Riwan (Universitas Negeri Padang, 2014)
This Research is background of phenomenon found in country elementary school bunch I, II and III district batang cenaku sub-province of indragiri hulu riau which show there is still learn less of its motivation in working. This matter anticipated related to unfavourable organizational culture. This study aims to view relation organization culture with motivation work teacher country elementary school bunch I, II and III district batang cenaku sub-province of indragiri hulu riau. this research is all teacher with amount 118 people and 54 samples were taken with the Proportional stratified random sampling technique. The research instrument was a likert scale questionnaire form which has been in testing the validity and reliable. Technique analysis data use correlation formula of product moment. Results research this is motivation work teacher good enough cultural organization good and there are relation the signifikan between organizing cultural with work motivation good enough country elementary school bunch I, II and III district batang cenaku sub-province of indragiri hulu riau with correlation equal to 0,383. Kata kunci: Budaya organisasi; motivasi kerja